(The Effect of Ascorbic Acid and Sodium Erythorbate on Processing of Kolang-Kaling (Arenga pinnata Merr) in Syrup - Dwi Sutrsiniati; Harry Wiriano (Balai Besar Industri Agro, 1989)
Antioxidant were added to the processing of